2021
DOI: 10.1002/elsc.202000049
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cell productivity for the production of recombinant proteins by flow cytometry: An effective application using the cold capture assay

Abstract: Due to the increasing economic and social relevance of biotherapeutics, their production processes are continually being reconsidered and reoptimized in an effort to secure higher product concentrations and qualities. Monitoring the productivity of cultured cells is therefore a critically important part of the cultivation process. Traditionally, this is achieved by determining the overall product titer by high performance liquid chromatography (HPLC), and then calculating the specific cell productivity based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The total protein concentration of the supernatant was analyzed by high-performance liquid chromatography (HPLC) as described by Meyer et al and used for calculation of the mAb peak proportions. [22] Antibody bioactivity was determined by an adherent mouse fibroblast (L929) cell based assay using the tumor necrosis factor alpha (TNF-α) under the presence of actinomycin D. [23] Therefore, L929 cell viability was analyzed using the cell titer-blue assay (Promega, USA) after 24 h of antigen/antibody treatment. The produced antibody was diluted and used in low and high concentrations of 2.5 and 50 ng/mL respectively.…”
Section: Analyticsmentioning
confidence: 99%
“…The total protein concentration of the supernatant was analyzed by high-performance liquid chromatography (HPLC) as described by Meyer et al and used for calculation of the mAb peak proportions. [22] Antibody bioactivity was determined by an adherent mouse fibroblast (L929) cell based assay using the tumor necrosis factor alpha (TNF-α) under the presence of actinomycin D. [23] Therefore, L929 cell viability was analyzed using the cell titer-blue assay (Promega, USA) after 24 h of antigen/antibody treatment. The produced antibody was diluted and used in low and high concentrations of 2.5 and 50 ng/mL respectively.…”
Section: Analyticsmentioning
confidence: 99%
“…A variety of in vitro methods are available for testing cytotoxic effects, ranging from counting viable/dead cells under the microscope to biochemical assays, flow cytometric analysis, and real-time live-cell imaging technology [33,[35][36][37]. While microscopic observations -including counting of viable/dead cells using vital dyes such as trypan blue -and observations of changes in cell morphology provide an initial assessment of cytotoxic effects, biochemical assays provide more reliable and specific information [33,35,36].…”
Section: Practical Applicationmentioning
confidence: 99%
“…As a result, a standardized VCC would yield a higher product titer. Previous studies showed an increase in productivity during the stationary phase and the transition phases into and out of it [19]. Importantly, the methods applied in this second approach should not impair cell growth in its exponential phase to ensure high cell concentrations during the time of highest productivity.…”
Section: Introductionmentioning
confidence: 98%